2009
DOI: 10.1175/2009jpo4041.1
|View full text |Cite
|
Sign up to set email alerts
|

Wave-Driven Inner-Shelf Motions on the Oregon Coast*

Abstract: Recent work by S. Lentz et al. documents offshore transport in the inner shelf due to a wave-driven return flow associated with the Hasselmann wave stress (the Stokes-Coriolis force). This analysis is extended using observations from the central Oregon coast to identify the wave-driven return flow present and quantify the potential bias of wind-driven across-shelf exchange by unresolved wave-driven circulation. Using acoustic Doppler current profiler (ADCP) measurements at six stations, each in water depths of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 26 publications
(71 reference statements)
2
27
0
Order By: Relevance
“…To further isolate the effects of surface wave forcing, Eulerian velocity profiles during low wind and large wave forcing are examined relative to the mean velocity profiles during low wind and small wave forcing, following Lentz et al (2008) and Kirincich et al (2009). The observed flow during low wind and small wave conditions is assumed to represent the effects of other processes (e.g., pressure gradient forcing) not correlated with wave and wind forcing, and not directly measured as part of this study.…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further isolate the effects of surface wave forcing, Eulerian velocity profiles during low wind and large wave forcing are examined relative to the mean velocity profiles during low wind and small wave forcing, following Lentz et al (2008) and Kirincich et al (2009). The observed flow during low wind and small wave conditions is assumed to represent the effects of other processes (e.g., pressure gradient forcing) not correlated with wave and wind forcing, and not directly measured as part of this study.…”
Section: Observationsmentioning
confidence: 99%
“…Recent studies suggest that wave-driven undertow can be a significant part of the cross-shore Eulerian circulation just beyond the surf zone Kirincich et al 2009). During weak wind forcing, mean observed Eulerian velocities associated with wave forcing at the 10-m isobath are ,1 cm s 21 .…”
Section: Conclusion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…A compensating wave-driven offshore Eulerian flow u E (z) exists below the wave trough, referred to as undertow. The presence of wave-driven Eulerian undertow inside the surf zone is widely known and has been measured extensively in the field (Haines and Sallenger 1994;Garcez Faria et al 2000;Reniers et al 2004b) and has also been found to extend well offshore on the inner shelf (Lentz et al 2008;Kirincich et al 2009;Ohlmann et al 2012). The summation of u St (z) and u E (z), throughout the water column at a given location, results in a wave-averaged Lagrangian velocity u L (z), where z is the vertical elevation defined as positive upward from the sea surface.…”
Section: Introductionmentioning
confidence: 99%
“…During this deployment the average SWH, peak wave period (PWP, calculated from the 1D frequency spectrum using a parabolic fit around the discrete peak), and peak wave direction (PWD, calculated from the 1D direction spectrum in the same fashion as PWP) were 2.5 m, 11.1 s, and 2918, respectively. The maximum recorded SWH during this experiment was 6.8 m while the longest PWP was 19.9 s. The NP05 data consist of an initial deployment (NP05S) near Newport, Oregon, at 15-m water depth from 15 June to 13 July 2005 [for a complete description of the data collection from this experiment, the reader is referred to Kirincich et al (2009)]. During the deployment time the instrument recorded average SWHs, PWPs, and PWDs of 1.3 m, 8.5 s, and 2848, respectively.…”
Section: A Data Sourcesmentioning
confidence: 99%